Immigration, Racial Profiling, and White Privilege: Community-Based Challenges and Practices for Adult Educators - Luis Kong (Adult Education Research Conference, 2010)
This study explores the significance of race from a social constructionist perspective. Examples of legal cases set the stage for current definitions of whiteness and racial identification. A community-based transformational organizing model is explained by describing the challenges and educational strategies used by an immigrant rights organization. The conclusion will reflect on how and in what ways this transformative, organizing approach involves relational and contextual dialogue to build a community of learners through action.